Thematic Classification in Polish Electronic Dictionaries — From Tradition to New Tools and Opportunities - Batko-Tokarz, Barbara (Lexikos, 2025)
The main topic of this article is the thematic classification of vocabulary in two Polish dictionaries that were compiled at the beginning of the 21st century. The first is the Wielki sÅ‚ownik jÄ™zyka polskiego PAN (WSJP PAN) [The Polish Academy of Sciences Great Dictionary of Polish], which describes contemporary vocabulary and can function as a thematic dictionary. The second is the SÅ‚ownik pojÄ™ciowy jÄ™zyka staropolskiego (SPJS) [Conceptual Dictionary of Old Polish], which collects vocabulary up to the end of the 15th century and arranges it in conceptual fields. The primarily electronic format of these dictionaries has created completely new possibilities for classification according to meaning, which is worth briefly describing in the context of the thematic lexicography used in Polish paper dictionaries to date. Therefore, the most important Polish thematic dictionaries over the centuries are listed first (Section 2), followed by a more detailed description of the SPJS and WSJP PAN (Section 3). In Section 4, the following is described based on these two Polish electronic dictionaries: the ease of switching between onomasiological and semasiological orders, the significantly greater possibilities for classifying linguistic materials, and the ability to search fields using advanced search functions. These considerations are important given the growing number of electronic dictionaries increasingly adopting onomasiological orders.Keywords: onomasiological lexicography, thematic lexicography, thematic dictionaries, concept dictionaries, primarily electronic dictionaries, search tools in electronic dictionaries, onomasiological and semasiological order, thematic classification of vocabulary